AN ANALYSIS OF STUDENTS' READING COMPREHENSION IN USING IRAS (INTERACTIVE READ ALOUD STRATEGY) - Hira, Salma; Ngaisah, Siti; Dewi, Ekka Zahra Puspita (Pusat Pengembangan Pendidikan dan Penelitian Indonesia, 2025)
Reading means opening a text that presents information, whether in print or non-print media. Students are always required to understand the material taught by their teachers. Currently, many students are very reluctant to read texts, especially books. They lack interest in reading textbooks or English books. Reading materials such as comics, novels, and short stories are more popular with today's students. Therefore, as researchers, we strive to gather information directly from students to gather data. This data relates to how students learn to read in English classes and what techniques English teachers use to engage them. Here, the researchers analyzed the use of interactive read-aloud strategies. The subjects of this study were English teachers and first-grade students at Al Islah Islamic Elementary School. The research method used was a qualitative case study design. The case study in this research has unique subjects: first-grade students at Al Islah Islamic Elementary School, who are still in the transition from Early Childhood Education to Elementary School. Naturally, their ability to comprehend texts is still not optimal. Therefore, they need guidance from their English teachers to improve their mastery of reading texts. The informants for this study were teachers and first-grade students of SDI Al Islah, using interviews, observation sheets, and documents as instruments. The observations revealed that English teachers used the following steps: creating lesson plans, developing strategy rules, developing strategy materials, developing learning media, evaluating, and providing feedback. Based on the explanation above, the interactive read-aloud strategy contributes to students' reading comprehension. This strategy can improve students' listening skills, recognize expressions, enrich vocabulary, motivate students to read English texts, and improve reading comprehension. ABSTRAKMembaca berarti membuka suatu teks yang menyajikan informasi baik dalam media cetak maupun non cetak. Kegiatan membaca selalu dibutuhkan oleh siswa untuk memahami materi yang diajarkan oleh gurunya. Saat ini banyak siswa yang sangat enggan untuk membaca teks apalagi buku. Mereka kurang berminat untuk membaca seperti buku pelajaran atau buku bahasa Inggris. Bacaan seperti komik, novel dan cerpen lebih diminati oleh siswa masa kini. Itulah sebabnya sebagai peneliti kami berusaha menggali informasi dari siswa secara langsung untuk mencari data. Data ini terkait dengan bagaimana siswa belajar membaca di kelas bahasa Inggris dan teknik apa saja yang digunakan guru bahasa Inggris untuk membuat mereka tertarik. Di sini peneliti menganalisis penggunaan strategi membaca nyaring interaktif. Subjek penelitian ini adalah guru bahasa Inggris dan siswa kelas satu di Sekolah Dasar Islam Al Islah. Metode penelitian yang digunakan adalah kualitatif dengan rancangan studi kasus. Studi kasus dalam penelitian ini memiliki subjek yang unik yaitu siswa kelas I SD Islam Al Islah yang kebetulan masih dalam masa transisi dari Pendidikan Anak Usia Dini ke jenjang Sekolah Dasar. Tentunya kemampuan dalam memahami suatu teks masih belum optimal. Sehingga mereka membutuhkan bimbingan dari guru Bahasa Inggrisnya dalam meningkatkan penguasaan teks bacaan. Informan penelitian ini adalah guru dan siswa kelas I SDI Al Islah dengan menggunakan instrumen wawancara, lembar observasi dan dokumen. Dari observasi tersebut ditemukan data bahwa guru Bahasa Inggris menggunakan langkah-langkah yang terdiri dari: membuat rencana pembelajaran, aturan strategi, materi strategi, media pembelajaran, evaluasi dan umpan balik. Berdasarkan penjelasan di atas, strategi membaca nyaring interaktif berkontribusi pada pemahaman siswa terhadap bacaan. Strategi ini dapat meningkatkan keterampilan mendengarkan siswa, mengenal ungkapan, memperkaya kosakata, memotivasi siswa untuk membaca teks bahasa Inggris, dan berhasil dalam pemahaman bacaan.